Social Science Teachers’ Pedagogical Content Knowledge: A Case Study At General Secondary School Level In Bangladesh - Zinnah, Mohammad Ali (2010)
This multiple-case study investigates Social Science teachers’ Pedagogical Content Knowledge (PCK), and factors that facilitate or inhibit their PCK in teaching Social Science at the general secondary level education in Bangladesh. Shulman’s (1987) model of Pedagogical Reasoning and Action was used as the theoretical model in this study. Five teachers were purposeful selected from one government, three non-government and one specialized general secondary schools to participate in this the study. Multiple techniques including pre- and post-observation interviews with the teacher participants, observations of their classroom teaching, and analysis of documents were used for collecting the data. Nineteen other informants were selected to gain further data through interviewing. Data were analyzed during the period of data collection to develop deeper understanding of the phenomena under investigation, as well as to guide in seeking appropriate data from the participants. The final data were analyzed in different steps to arrive at the findings. The validity and reliability of the data and the findings were maintained. The findings have demonstrated eight components of PCK that the participants possessed and practiced, but not at equal level.